Perancangan Tas Perlengkapan Anak Multifungsi Berkonsep Backpack - Tri Indriyani Nandasari; Putri Angraeni Widyastuti (Student Research Journal, 2026)
Children's Equipment Bag is a means to store and carry children's equipment while traveling. Usually our view on a children's bag is in the form of a sling bag and with animal or cartoon motifs but it is less attra active and also has a monotonous design if you have to take it when traveling with your little one. What is needed is a children's bag with a shape that can be adapted to consumer needs and its function is not only a place to store and carry children's equipment, but this bag can also be used in all activities with new innovations. Based on these problems, researchers will innovate with the design of children's bag products using synthetic leather material with a space-themed backpack model. but will also be an attraction for consumers.